Training effects of plyometric training on jump parameters in D- and D/C-squad badminton players - Fröhlich, M.; Felder, H.; Reuter, M. (Journal of Sports Research, 2014)
Plyometric training is popular among individuals involved in dynamic sports, and plyometric exercises such as jumping, hopping, skipping and bounding are executed with the goal of increasing dynamic muscular performance, especially jumping. Much less information is available on the effectiveness of plyometric training (PT) in badminton, where jumping high (e.g. forehand overhead jump-smash) is important for success. The aim of the study was to investigate the effects of an 8-week periodized PT program on jumping high and power among male and female junior badminton players, using high-impact bilateral plyometric exercises. Starting and finishing with the biomechanical diagnostics of the squat jump (SJ), counter movement jump (CMJ), and drop jump (DJ) on force plates, kinematic analysis of forehand overhead smashes, anthropometric data as well as force data for pre- and posttest were analyzed. Before and after the biomechanical diagnostics, the players (n=11) undergo an 8-week PT (2 units per week) with a total of 2286 jumps. 8 male and 3 female junior badminton players (age: 16.0±1.6 years, height: 175.5±9.9 cm, mass: 69.3±11.4 kg) were tested in jumping high and forehand overhead jump-smashes performance. Looking at the plyometric strength parameters of the squat jump (P 0.05). Therefore, the focus must be on technical training. Consequently, it is considered to be important to include short-term PT in in-season preparation in order to improve complex badminton-specific dynamic performance (smash-jumping).